Branding and positioning strategies in Public Technological Higher Education Institutes - Gamonal Montoya, José Alberto (2022)
The purpose of the study is to know the relationship between branding and positioning strategies in the Higher Technological-Pedagogical Education Institutes (IESTP) of South Lima. The methodology used is of an applied type, a quantitative approach and a non-experimental - correlational design. A questionnaire was applied to a sample of 268 school graduates. A positive mean relationship was concluded (Spearman's Rho = 0.5), which means that the IESTPs are not performing good strategic positioning management, so the implementation of a marketing unit is recommended so that a value of brand that can position itself in the minds of future applicants. In general, the evaluation of the Brandy has a medium relationship with the positioning strategies in the IESTP (locations in South Lima). Spearman's Rho coefficient is 0.498, which shows a positive relationship and at a medium level.